2009
DOI: 10.1002/cjoc.200990347
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Copper and Zinc Ions by Flame‐AAS After Preconcentraction Using Sodium Dodecyl Sulfate Coated Alumina Modified with 3‐((1H‐Indol‐3‐yl)‐3,4,5‐trimethyl)‐1H‐indole

Abstract: A sensitive and simple method for the simultaneous preconcentration of trace amount Cu 2+ and Zn 2+ ions in some real samples has been established, which is based on the sorption of Cu 2+ and Zn 2+ on 3-((1H-indol-3-yl)-3,4,5-trimethyl)-1H-indole (ITMI) loaded on sodium dodecyl sulfate (SDS) coated alumina. The metal absorbed on the complexes was eluted using 3 mol/L nitric acid. The influences of the analytical parameters including pH and sample volume were investigated. The effects of matrix ions on the ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Ghaedi et al , have used BIMs coated on an alumina−sodium dodecyl sulfate (SDS) surface for preconcentration and determination of Cu(II), Zn(II), Pb(II), and Fe(III) ions by flame atomic absorption spectrometry. Also BIMs and TIMs have been used as ligands for the synthesis of more complex molecules, and different properties of these complexed molecules have been investigated. …”
Section: Introduction and Importance Of Bis- And Trisindolylmethanes ...mentioning
confidence: 99%
“…Ghaedi et al , have used BIMs coated on an alumina−sodium dodecyl sulfate (SDS) surface for preconcentration and determination of Cu(II), Zn(II), Pb(II), and Fe(III) ions by flame atomic absorption spectrometry. Also BIMs and TIMs have been used as ligands for the synthesis of more complex molecules, and different properties of these complexed molecules have been investigated. …”
Section: Introduction and Importance Of Bis- And Trisindolylmethanes ...mentioning
confidence: 99%
“…50 We determined the copper content in benzimidazole 3a by using Atomic Absorption Spectroscopy after purification by column chromatography. 51 The analysis showed that the product obtained from the reaction catalysed by our CeCl 3 •7H 2 O-CuI system was contaminated with only 11 ppm of copper, a value much below what can be obtained in other methods of synthesis of N-heterocycles by copper catalysts. 52 With an efficient procedure in hand for obtaining 2-substituted benzimidazoles, we decided to explore the synthetic application of our methodology.…”
Section: Resultsmentioning
confidence: 72%
“…Therefore, it is of great importance to develop simple, rapid and precise sensor methods to detect and monitor the concentration of Cu 2+ . Currently, there are many analytical methods for detecting Cu 2+ , such as atomic absorption spectroscopy (AAS) [ 3 ], inductive coupled plasma-mass spectroscopy (ICP-MS) [ 4 ], and fluorescence and surface plasmon resonance sensor methods [ 5 , 6 , 7 ]. Among these methods, fluorescence sensing remains one of the most promising approaches due to its high sensitivity, rapid response, and high selectivity through molecular binding design, as well as its simple solution assay processing [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%